Importance of airflow for physiologic and ergogenic effects of precooling - Morrison, S. A.; Cheung, S.; Cotter, J. D. (Journal of Athletic Training, 2015)
Context: Cooling the body before exercise (precooling) has been studied as an ergogenic aid for many thermal conditions; however, airflow accompanying exercise is seldom reported.